Neighbourhood walkability and body mass index in children: Evidence from the Millennium Cohort Study in Wales - Dora Pouliou (Journal of Transport & Health, 2024)
Background: Overweight and obesity in children continues to increase. Yet, the role of active transport, namely walking, in mitigating these trends remains unclear. This study examined the cross-sectional association between walkability and children’s Body Mass Index (BMI) and how this varies by socio-economic and lifestyle characteristics. Methods: We analysed BMI for 14-year-old children living in Wales from the UK Millennium Cohort Study. Children were categorised as healthy weight, overweight or obese using the British 1990 cut-off points. Walkability was assessed using the Wales Active Living Environments (Wal-ALE) database, categorised as 1 (least walkable environments) to 5 (most walkable environments). We applied multinomial logistic regression analysis and adjusted for ethnicity, having a limiting longstanding illness, parental BMI, socio-economic circumstances, and lifestyle characteristics. Results: Children were more likely to be obese if they lived in areas classed as more walkable in unadjusted analysis [Relative Risk Ratio (RRR)=1.72 (95% CI =1.15 - 2.58)] and following adjustment for ethnicity, limiting longstanding illness and parental BMI [RRR= 1.83 (95%CI=1.12 – 3.00)].). Significant associations remained even after further adjustment for lifestyle characteristics and socio-economic circumstances [RRR=1.76 (95%CI=1.05 – 2.96)]. Further, children were more likely to be obese if their parents were overweight or obese and if they were living in poverty. Children were less likely to be obese if they spent 3 or more days per week in moderate-to-vigorous physical activity (MVPA) and if they ate breakfast every day vs. some days or never. Conclusion: Findings demonstrate that walkable environments are not associated with lower rates of obesity in children, indicating that the relationship between the built environment and child health is complex and requires further study.